Neutrophil extracellular traps are involved in the innate immune response to infection with Leptospira - Scharrig Fernandez, Maria Emilia (2015)
NETosis is a process by which neutrophils extrude their DNA together with bactericidal proteins that trap and/or kill pathogens. In the present study, we evaluated the ability of Leptospira spp. to induce NETosis using human ex vivo and murine in vivo models. Microscopy and fluorometric studies showed that incubation of human neutrophils with Leptospira interrogans serovar Copenhageni strain Fiocruz L1-130 (LIC) resulted in the release of DNA extracellular traps (NETs). The bacteria number, pathogenicity and viability were relevant factors for induction of NETs, but bacteria motility was not. Entrapment of LIC in the NETs resulted in LIC death; however, pathogenic but not saprophytic Leptospira sp. exerted nuclease activity and degraded DNA. Mice infected with LIC showed circulating NETs after 2 days post-infection (dpi). Depletion of neutrophils with mAb1A8 significantly reduced the amount of intravascular NETs in LIC-infected mice, increasing bacteremia at 3 dpi. Although there was a low bacterial burden, scarce neutrophils and an absence of inflammation in the early stages of infection in the kidney and liver, at the beginning of the leptospiruric phase, the bacterial burden was significantly higher in kidneys of neutrophil-depleted-mice compared to non-depleted and infected mice. Surprisingly, interstitial nephritis was of similar intensity in both groups of infected mice. Taken together, these data suggest that LIC triggers NETs, and that the intravascular formation of these DNA traps appears to be critical not only to prevent early leptospiral dissemination but also to preclude further bacterial burden.